Green Synthesis of Magnetic Iron Oxide Nanoparticle for Antibacterial Activity: A Review: Review: Nano-Technology Use in Green Synthesis (Biological Sciences - PJSIR, 2021)
Recently, different researchers find nanoparticles as an auspicious alternative to antibacterial agents due to their antibacterial behaviour. This antibacterial behaviour contributes in many biomedical applications including; tissue engineering, drug and gene delivery and, imaging. Furthermore, iron oxide nanoparticle gains much importance due to their magnetic characteristics and wide range of application. Iron oxide nanoparticle (IONPs) have exhibits great potential against bacteria. During the past decade, various routes were developed to synthesize iron oxide nanoparticle with suitable size and composition. This article reviews the recent iron oxide nanoparticle obtained by green synthesis with a focus on their response to antibacterial activities. The iron nanoparticles synthesized by green synthesis method has accumulated a vital attention over the last couple of years due to their unique characteristic as it makes sure environmental friendly, nontoxic and safe reagents.